1996
DOI: 10.1515/hfsg.1996.50.3.269
|View full text |Cite
|
Sign up to set email alerts
|

Water Absorption and Contact Angle Measurement of Native European, North American and Tropical Wood Species to Predict Gluing Properties

Abstract: In order to optimize the gluing performance of wood splints with KPVAC-glues, it is of utmost importance to know the amount of water able to penetrate into the gluable wood splints. Therefore, in this study two techniques to measure the water absorption ability of building materials were applied on a variety of 40 representative tropical and native European wood species. The first method is a common German standard and measures the water absorption coefficient w t . The second is based on the determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 2 publications
1
17
0
5
Order By: Relevance
“…Buyuksari et al (2011) obtained the contact angle from the average of measurements over a 10-s period to investigate the wettability and surface roughness of natural and plantation-grown narrow-leaved ash wood. Boehme and Hora (1996) observed that the contact angle decreased with the square root of time, while Shi and Gardner (2001) proposed a Shi-Douglas wetting model (S-D model) that is commonly used to evaluate the dynamic wetting process.…”
Section: Introductionmentioning
confidence: 99%
“…Buyuksari et al (2011) obtained the contact angle from the average of measurements over a 10-s period to investigate the wettability and surface roughness of natural and plantation-grown narrow-leaved ash wood. Boehme and Hora (1996) observed that the contact angle decreased with the square root of time, while Shi and Gardner (2001) proposed a Shi-Douglas wetting model (S-D model) that is commonly used to evaluate the dynamic wetting process.…”
Section: Introductionmentioning
confidence: 99%
“…References for the Data Given in Table 1 Picea abies (Kramer et al 1988;Hasler et al 1994;Boehme and Hora 1996;Mantanis and Young 1997;Nurmi 1997;Bergh et al 1999;Nussbaum 1999;de Meijer et al 2000;Lässig and Močalov 2000;Balode et al 2002;Schulze et al 2002;Matthews and Mackie 2006;Rutz et al 2006;Kaltschmitt et al 2009;Sernek et al 2010;Günther et al 2012;Karl 2012;Navi and Sandberg 2012;EngineeringToolBox 2013) Pinus sylvestris (Bray 1963;Kramer et al 1988;Hasler et al 1994;Wilén et al 1996;Nurmi 1997;Nussbaum 1999;Lässig and Močalov 2000;Schulze et al 2002;Xiao et al 2003;Mohammed-Ziegler et al 2004;Kaltschmitt et al 2009;Karl 2012;Navi and Sandberg 2012;Sedighi et al 2012) Abies alba (Bray 1963;Kramer et al 1988;Becker 1989;de Meijer et al 2000;Lässig and Močalov 2000;Schulze et al 2002;Macias et al 2006;Matthews and Mackie 2006;Wagenführ 2007;…”
Section: Methodsunclassified
“…(Bray 1963;Kramer et al 1988;Paavilainen and Torgilsson 1994;Syrjanen et al 1994;Nurmi 1997;Lässig and Močalov 2000;Schulze et al 2002;Stener and Hedenberg 2003;Matthews and Mackie 2006;Wagenführ 2007;Kaltschmitt et al 2009;Sernek et al 2010;Günther et al 2012;Karl 2012;Viöl et al 2012;EngineeringToolBox 2013;PaperonWeb 2013) Alnus glutinosa (Kramer et al 1988;Nurmi 1997;Johansson 2000;Schulze et al 2002;Mohammed-Ziegler et al 2004;Wagenführ 2007;Kaltschmitt et al 2009;Kiaei and Samariha 2011;Karl 2012) Populus spp. (Boehme and Hora 1996;Diamantidis and Koukios 2000;Barsoum 2001;Deiller et al 2001;Benetka et al 2002;Laureysens et al 2003;Helle and Schleser 2004;Matthews and Mackie 2006;Rutz et al 2006;Wagenführ 2007;Trnka et al 2008;Kaltschmitt et al 2009;Petrič et al 2009;Sernek et al 2010;Ráhel' et al 2011;Karampinis et al 2012;Karl 2012;...…”
Section: Methodsunclassified
See 2 more Smart Citations